Evaluation of fisheries management strategies using a biotic integrity index in floodplain lakes in the lower Solimões River, Amazonas, Brazil - Bruna de Souza ANDRADE; Carlos Edwar de Carvalho FREITAS; Maria Letizia PETESSE; Flávia Kelly SIQUEIRA-SOUZA (Acta Amazonica, 2022)
ABSTRACT Fisheries is an important activity in the Amazon basin and potentially has a high impact on ichthyofauna. With the aim of achieving sustainability in fisheries of target species, protected areas were established within a fisheries management framework known as the Amazon Lakes Management System (ALMS). With the aim to evaluate the effect of ALMS on fish assemblages as a whole, we compared floodplain lakes with different levels of fish management in the lower Solimões River, in the Brazilian Amazon, developing an index of biotic integrity, named ALMS-IBI. We sampled fish in three lake categories: protected (PR), managed (MN), and commercially fished (CM). The ALMS-IBI was developed by selecting and testing fish assemblage metrics based on samplings carried out in 2017 and 2018, using gillnets with different mesh sizes. We captured 4565 fish of 113 species and seven trophic categories. The final index is composed of seven metrics related to species richness, trophic structure, and fish abundance, and characterized the fish assemblage in the PR and MN lakes as acceptable, and in the CM lakes as poor. Our results indicate that the ALMS-IBI can be an efficient method to monitor the whole fish assemblage in Amazonian floodplain lakes, and can be used as a complementary tool in the ALMS to assess environmental sustainability.